Coherency strengthening of oblate precipitates extended in the {100} plane of fcc crystals: Modeling and experimental validation - Ahmadi M.R.; Sonderegger B.; Povoden-Karadeniz E.; Falahati A.; Yadav S.D.; Sommitsch C.; Kozeschnik E. (My University, 2025)
Coherency strengthening plays a major role in precipitation strengthening. The governing mechanism is based on the interaction of dislocations with the elastic strain field induced by the lattice misfit of precipitates and matrix. In the case of non-spherical precipitates, the strain field and corresponding stress field is inhomogeneous and depends on the relative orientation of the particle with respect to the Burger's vector of the dislocation. We evaluate the shear stress increment due to inhomogeneous strain fields around an oblate precipitate and suggested a model for coherency strengthening of oblate precipitates. The corresponding results for the weak and strong strengthening mechanisms demonstrate that shape-depending correction factors need to be incorporated in order to estimate the strength precisely. Afterwards, the proposed model was applied for simulation of precipitation strengthening of Inconel 718. Simulation result shows that, the selection of correct aspect ratio can lead to more accurate yield strength predictions that are close to the experimental results. © 2022 The Author(s)